Non‐random distribution of deleterious mutations in the DNA and protein‐binding domains of IRF6 are associated with Van Der Woude syndrome. Issue 8 (17th June 2020) - Alade, Azeez A.; Buxo‐Martinez, Carmen J.; Mossey, Peter A.; Gowans, Lord J.J.; Eshete, Mekonen A.; Adeyemo, Wasiu L.; Naicker, Thirona; Awotoye, Waheed A.; Adeleke, Chinyere; Busch, Tamara; Toraño, Ada M.; Bello, Carolina A.; et al.
Abstract: Background: The development of the face occurs during the early days of intrauterine life by the formation of facial processes from the first Pharyngeal arch. Derangement in these well‐organized fusion events results in Orofacial clefts (OFC). Van der Woude syndrome (VWS) is one of the most common causes of syndromic cleft lip and/or palate accounting for 2% of all cases. Mutations in the IRF6 gene account for 70% of cases with the majority of these mutations located in the DNA‐binding (exon 3, 4) or protein‐binding domains (exon 7–9). The current study was designed to update the list of IRF6 variants reported for VWS by compiling all the published mutations from 2013 to date as well as including the previously unreported VWS cases from Africa and Puerto Rico. Methods: We used PubMed with the search terms; "Van der Woude syndrome, " "Popliteal pterygium syndrome, " "IRF6, " and "Orofacial cleft" to identify eligible studies. We compiled the CADD score for all the mutations to determine the percentage of deleterious variants. Results: Twenty‐one new mutations were identified from nine papers. The majority of these mutations were in exon 4. Mutations in exon 3 and 4 had CADD scores between 20 and 30 and mutations in exon 7–9 had CADD scores between 30 and 40. The presence of higher CADD scores in the protein‐binding domain (exon 7–9) further confirms the crucial role played by this domain in the function of IRF6. In the new cases, we identified five IRF6 mutations, three novel missense mutations (p.Phe36Tyr, p.Lys109Thr, and p.Gln438Leu), and two previously reported nonsense mutations (p.Ser424*and p.Arg250*). Conclusion: Mutations in the protein and DNA‐binding domains of IRF6 ranked among the top 0.1% and 1% most deleterious genetic mutations, respectively. Overall, these findings expand the range of VWS mutations and are important for diagnostic and counseling purposes. Abstract : The study reported novel variants in IRF6 from patients with VWS. Updated the list of all IRF6 variants reported from 2013 to date and provide an insight into on how to use the Combined Annotation Dependent Depletion score for the prioritization of IRF6 variants.